Was ist Stadtökologie? Argumente für eine Erweiterung des Aufmerksamkeitshorizonts ökologischer Forschung - Hard, Gerhard (ERDKUNDE, 1997)
At first some different interpretations of the term urban ecology are discussed. Secondly, it is shown by the use of common, well known geobotanical phenomena within urban areas that a strict natural science approach to urban ecology will in many cases obscure rather than explain ecological phenomena and problems. The reason for this can be seen in the fact that the actual state, the change and the variability of ecological phenomena are dependent not only on the natural conditions, but also on the (socially determined) interpretations in terms of different symbolic ecologies. For an ecological biologist it is therefore also necessary to take into account the ethno-ecology (the symbolic ecology or political ecology) of his subjects. This means the ecologist must observe in his research practice: 1. the real ecological situation as it is perceived in the natural sciences; 2. how people perceive and interpret ethno-ecologically the ecological situation (and who sustain these ethno-ecologies); 3. the relationship between the real ecology and the symbolic ecologies; 4. how people behave and act on the basis of their symbolic ecology; 5. the result of their behaviour and actions with regards to the real ecology; 6. how this result of often unreal ecologies is being perceived, interpreted and legitimated. Of course, the discipline of ecology will in most cases concentrate on the research questions (1) and (5), which can be answered by applying the methodology of the natural sciences. But in the paper it is argued that the other research questions have also to be addressed. An ecology of the proposed broader type represents a hybrid paradigm, which is similar in structural terms to the paradigms of classical geography and traditional vegetation studies. Finally, it is argued that the ecologist should act more as an independent observer and critical evaluator of political and administrative actions rather than as an adviser to the political-administrative system and its decision making.